Specific Methodological Principles of Teaching A Foreign Language (Eurasian Journal of Learning and Academic Teaching, 2021)
The article discusses the methodological principles in more detail that describe and concretize the specifics of teaching a foreign language. This group includes the principle of communicative orientation, taking into account the peculiarities of the native language, the principle of interconnected teaching of all types of speech activity, the principle of functionality, oral advance, approximation, as well as a number of other principles that are formulated by the authors depending on the chosen approach to teaching.